Вы находитесь на странице: 1из 1

Solution (proof) 1. a) Assume that n is odd, so n = 2k + 1 for some integer k. Then n3 + 5 = 2(4k3 + 6k2 + 3k + 3).

Since n3 + 5 is two times some integer, it is even. b) Suppose that n3 + 5 is odd and n is odd. Since n is odd and product of two odd numbers is odd, it follows that n2 is odd and then that n3 is odd. But then 5 = (n3 + 5) - n3 would have to be even since it is the difference of two odd numbers. Therefore, the supposition that n3 + 5 and n were both odd is wrong. 2. Let n = 2k + 1 and m = 2l + 1 be odd integers. Then n + m = 2(k + l + 1) is even. 3. If x y, then max(x, y) + min(x, y) = y + x = x + y. If x y, then max(x, y) + min(x, y) = x + y. Since these are the only two cases, the equality always holds. 4. There are three cases to consider: Case 1, a is smallest, or tied for smallest; Case 2, b is smallest, or tied for smallest; Case 3, c is smallest, or tied for smallest. Since one of a, b, and c is smallest, or tied for smallest, these three cases cover all possibilities. In case 1, a min(b, c), so the left-hand side is a and the right-hand side is also a since min(a, c) = a. The argument in the other two cases is similar. 5. Let P(n) be 2n > n2. Basis step: P(5) is true since 25 = 32 > 25 = 52. Inductive step: Assume that P(n) is true, that is 2n > n2. Then 2n+1 = 22n > n2 + n2 > n2+ 4n n2 + 2n + 1 = (n+1)2 since n > 4. 6. Let P(n) be 1 2 + 2 3 + + n(n + 1)= n(n + 1)(n + 2)/3. Basic step: P(1) is true since 1 2= 2 = 1(1 + 1)(1 + 2)/3. Inductive step: Assume that P(n) is true. Then 12 + 23 + + n(n + 1)+ (n+1)(n+2) = [n(n + 1)(n + 2)/3] + (n + 1)(n + 2) = (n + 1)(n+2) [(n/3) + 1]= (n + 1)(n + 2)(n + 3)/3